PERILAKU PEGAWAI DAN DAMPAKNYA PADA EFEKTIVITAS TENAGA KEPENDIDIKAN - Zainul Mohammad (At-Tadbir : jurnal ilmiah manajemen, 2020)
The public spotlight on performance is getting bigger, especially regarding the sub-optimal and the minimum standard of apparatus performance. Therefore attention to the performance and effectiveness of the organization's work is a central topic to be a busy topic of discussion. This study examines the extent of the influence of employee performance on the organizational effectiveness of the District Education Office of Tanah Bumbu. To administer this condition, the apparatus's behavioral dimensions include abilities, skills, knowledge, attitudes, and motivations while the dimensions of organizational effectiveness on work productivity, efficiency, and job satisfaction. Skills, knowledge, attitudes, and motivation as an organizational asset, so that the quality of the human resources of the organization concerned can be relied upon in carrying out work and readiness to face changes and challenges in the future.Keywords: Employee behavior, work effictiveness, performance, performance appraisal, HR quality